Lembaga Dana Pensiun Syariah sebagai Instrumen Perlindungan Masa Tua Berbasis Maqashid Syariah - Sari, Dian; Devy Wulandari; Andi Abdul Gaffar; Mukhtar Lutfi; Amiruddin Kadir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to understand the concept and regulations of Islamic pension funds (dana pensiun syariah) in Indonesia, which impact life in old age based on the Maqasid al-Shariah (objectives of Islamic law). An Islamic pension fund is a pension fund that administers a retirement program based on Sharia principles (DSN-MUI Fatwa Number: 88/DSN-MUI/XI/2013). The management of Islamic pension funds in Indonesia is carried out through investments in Sharia-compliant pension funds that are distributed to participants. This is closely tied to the contractual consequences of the underlying agreement governing the transactional relationship between DPLK (Financial Institution Pension Fund) participants and the Sharia DPLK, which is based on the contract of Wakalah bil Ujrah (agency with fee).This study uses a qualitative approach with a descriptive-analytical method to analyze instruments of old-age protection based on Maqasid al-Shariah in the management of pension funds within Islamic financial institutions. The research is rooted in the management of pension funds aligned with the Maqasid al-Shariah, which represent the main objectives of Islamic law—namely, to realize the welfare (maslahah) of humanity in both this world and the hereafter. This pension fund also serves as a form of old-age security designed to provide income certainty for workers after entering retirement.